Strategy of the Personnel and Human Resources Development Agency (BKPSDM) in Increasing the Value of the ASN Professionalism Index (IPASN) of the Denpasar City Government - Evi Wahyuningsih; Oka Martini (Green Publisher Indonesia, 2025)
The Civil Servant Professionalism Index (Indeks Profesionalitas Aparatur Sipil Negara or IP ASN) is a statistical measure that reflects the quality of ASN based on qualifications, competencies, performance, and discipline in carrying out their duties. This study aims to analyze the strategies of the Personnel and Human Resource Development Agency (Badan Kepegawaian dan Pengembangan Sumber Daya Manusia or BKPSDM) of Denpasar City in improving the IP ASN value. Using a qualitative descriptive method through interviews with key informants and the distribution of questionnaires to ASN, this research identifies internal and external factors affecting IP ASN. The results show that the competency dimension consistently receives the lowest scores, despite having the highest weight (40%) in IP ASN assessment. The main challenges include a lack of ASNawareness regarding competency development, inadequate data updating in personnel information systems, limited budget allocations for competency development, and incomplete system integration with Badan Kepegawaian Negara (BKN). Through SWOT analysis, this study recommends strategies focusing on strengthening non-classical training programs, intensive socialization, integration of personnel information systems, and optimization of Learning Management Systems (LMS) that are freely accessible. The findings contribute to the development of more effective human resource development strategies for enhancing ASN professionalism.